Strip Inter cropping - Double row and Four-row system: IPSR Innovation Profile - Thierfelder, Christian L. (2022)
Double-row strip cropping: This system reduces the plant spacing of maize rows to open up space for legumes to grow. Maize is usually intercropped with a legume (i.e., groundnuts/soya beans/cowpeas/beans). Maize is planted into rip lines opened in double rows (50cm inter-row x 25cm in-row) and a gap of 130cm is left in-between the maize double rows where legumes will be planted [groundnut (35cm inter-row x 30cm in-row); soya beans (35cm inter-row x 5cm in-row)] Four-row strip cropping: Similar to double row strip cropping above, four rows of maize alternate with four rows of a legume. However, the inter-row spacing of maize is reduced from the usual 90 cm to 45 cm. This narrowing and reduction in size increases growing space for four rows of legumes. Maize is planted into lines spaced at 45 cm interrow with 4 row strips of maize alternating with another 4 rows strip of soya beans/groundnuts also spaced at 45 cm between rows.